Identification and analysis of transepithelial transport properties of casein peptides with anticoagulant and ACE inhibitory activities. (December 2020) - Tu, Maolin; Liu, Hanxiong; Cheng, Shuzhen; Xu, Zhe; Wang, Li-Shu; Du, Ming
Graphical abstract: Highlights: Casein hydrolysate from the simulated GI tract showed anticoagulant and ACEI activities. Casein peptides existed before and after across the Caco-2 monolayer were identified. A novel method for screening bioactive peptides was established. Abstract: Casein is an excellent source for producing anticoagulant and angiotensin I-converting enzyme inhibitory (ACEI) peptides. Here, the anticoagulant and ACEI activities of the casein hydrolysate produced by in vitro simulated gastrointestinal (GI) digestion were evaluated. The casein hydrolysate showed potent anticoagulant activity by prolonging the thrombin time (TT) and activated partial thromboplastin time (APTT), and also presenting great ACEI activity, with an IC50 value of 0.52 mg mL −1 . Subsequently, the transepithelial transport properties of the casein hydrolysate were analyzed by using the Caco-2 cell monolayer model. The peptides profile of the casein hydrolysate before and after it passed across the Caco-2 cell monolayer were identified by NanoLC-Q-TOF-MS/MS. The results showed that a total of 121 and 184 peptides were identified before and after casein hydrolysate moved through the Caco-2 cell monolayer, respectively. Eighty peptides were presented at both time points of the transport study. Among the 80 peptides, 26 of them were screened with a high possibility of exerting physiological roles after they were absorbed into the blood by in silico methods, and the physicochemical characteristics, e . g ., hydrophobicity, net charge, and toxicity of the peptides also be evaluated. Our results provided a new prospect and approach for producing bioactive peptides from casein with anticoagulant and ACEI activities.